PELATIHAN KEWIRAUSAHAAN UNTUK MENGEMBANGKAN ENTERPRENEURSHIP MAHASISWA HUKUM EKONOMI SYARIAH STITNU SAKINAH DHARMASRAYA - Angel Sophia Intan; Asrizal; Laila Diana; Taufiqur Rahman; Marsya Benita; Devi Putri Meilani; Ama Safina; Alvin Hairi; Aldi Atmanegara; Astri Ivo; Ali Imran; Adrian Syah Rifa'I; Fadhil Daifullah; Sultan Diyas; Roland Anggala Perdana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Entrepreneurship education plays a crucial role in fostering students’ independence andcreativity, particularly among Islamic Economic Law students who are expected tounderstand both sharia principles and modern business practices. This study aims toanalyze the impact of entrepreneurship training on the development of entrepreneurialattitudes and interests among students of the Islamic Economic Law Department atSTITNU Sakinah Dharmasraya. Using a qualitative descriptive method with 18 studentsand 5 lecturers as participants from STITNU Sakinah Dharmasraya and IAKSS Bungo,data were collected through observation, interviews, and documentation. The results showsignificant changes: 77.8% of students experienced positive shifts in their perception ofthe business world, 72.2% expressed increased interest in developing independentbusinesses, and 66.7% planned to start their own ventures after participating in thetraining. These findings indicate that entrepreneurship training not only enhancesstudents’ knowledge but also motivates them to apply entrepreneurial values in practice.In conclusion, entrepreneurship training effectively contributes to the development ofentrepreneurial spirit among Islamic Economic Law students, making it a strategicprogram in preparing them for future challenges in the sharia-based business sector.